Energy-Efficient Transceiver Design for Full-Duplex Cooperative NOMA Systems with SWIPT - Yin, Xiaojuan; Wu, Wei; Dai, Haibo; Li, Pei; Wang, Baoyun (2018 10th International Conference on Wireless Communications and Signal Processing (WCSP), 2018)
A downlink cooperative non-orthogonal multiple access (CNOMA) system is investigated, wherein the near user acts as a full-duplex (FD) relay to assist the far user. The energy efficiency is to be maximized subject to QoS requirement of the far user and power budget constraints of the base station and the near user. Since the formulated problem is highly nonconvex, it is computationally challenging to be addressed. A low-complexity path-following algorithm is proposed, which invokes only one convex quadratic problem at each iteration. Numerical results demonstrate that the proposed algorithm outperforms the conventional iterative method.